Porokeratosis: Two Faces, One Family - S. Lembo; L. Panariello; L. Nugnes; C. Lembo; F. Alaya (Karger Publishers, 2009)
Porokeratosis is a disorder of keratinisation whose pathogenesis is yet unclear. It has been postulated that it results from the proliferation of an abnormal clone of keratinocytes, triggered by several factors, such as immunosuppression or prolonged ultraviolet exposure. Various clinical forms are recognized whose common denominator is a keratotic ring surrounding a central zone of atrophy. The histological hallmark is the cornoid lamella, a thin column of hyperproliferative abnormal keratinocytes. We describe two cases of porokeratosis. A 67-year-old woman with an erythematous purplish round plaque surrounded by a keratotic border that had appeared 6 years previously on the left sural region was diagnosed as 'giant' porokeratosis. A 49-year-old man presented with small papules coalescent in an erythematous oval plaque on the lateral side of the left foot consistent with linear porokeratosis.